ANALISIS KERUSAKAN JALAN DI RUAS SIMPANG BERENG BENGKEL TUMBANG NUSA - Ahmad Gama Feriko (Jurnal Teknologi Berkelanjutan, 2019)
The traffic volume on Jalan Simpang Bereng Bengkel - Tumbang Nusa Road is relatively dense with relatively heavy loads. Along with the time when there is a decrease in the value of the pavement construction, resulting in damage to the pavement. In the road section, a traffic lane has been widened, overlay pavement (overlay). In damaged road pavement areas, the repair is often carried out by patching (patching), but there is still damage to the road pavement in the section. Therefore it is necessary to conduct research on material savings and how to make improvements in accordance with applicable regulations or standards, with the addition of appropriate implementation costs. The research objective is to determine the type of damage, evaluate road damage. The results of the evaluation and analysis of the value of the pavement conditions with the method of asphalt institute MS-17 (Pavement Condition Rating / PCR), prevention of damage to segments/sta. 28 + 850 to 30 + 050 handling with overlays, segments / sta. 31 + 150 to 31 + 650 handling with overlay, and segment / sta. 33 + 500 to 33 + 700 handling with routine maintenance. The results of the analysis and evaluation of pavement thickness using the PtT-01-2002-B method, prevention of damage to segments/sta. 28 + 850 to 30 + 050 handling with overlays, segments / sta. 31 + 150 to 31 + 650 handling with overlay, and segment / sta. 33 + 500 to 33 + 700 handling with overlays. Segment pavement thickness/sta. 28 + 850 to 30 + 050 overlay with 23 cm thick asphalt concrete, overlay with a combination of 7 cm concrete asphalt and 46 cm LPA. Segment / sta. 31 + 150 to 31 + 650 overlay with 24 cm thick asphalt concrete, overlay with a combination of 7 cm concrete asphalt and 49 cm LPA. Segment / sta. 33 + 500 to 33 + 700 overlay with asphalt concrete thickness 28 cm, overlay with a combination of asphalt concrete 7 cm and LPA 61cm.